Discovery of potential competitive inhibitors against With-No-Lysine kinase 1 for treating hypertension by virtual screening, inverse pharmacophore-based lead optimization, and molecular dynamics simulations. Issue 2 (1st February 2022) - Jonniya, N.A.; Sk, M.F.; Roy, R.; Kar, P.
ABSTRACT: The With-No-Lysine (WNK) has received attention because of its involvement in hypertension. Genetic mutation in the genes of WNK, leading to its overexpression, has been reported in Familial Hyperkalaemic Hypertension, and thus WNK is considered a potential drug target. Herein, we have performed a high-throughput virtual screening of 11, 000 compounds, mainly the natural phytochemical compounds and kinase inhibitory libraries, to find potential competitive inhibitors against WNK1. Initially, candidates with a docking score of −10.0 kcal/mol or less were selected to further screen their good pharmacological properties by applying absorption, distribution, metabolism, excretion, and toxicity (ADMET). Finally, six docked compounds bearing appreciable binding affinities and WNK1 selectivity were complimented with 500 ns long all-atom molecular dynamic simulations. Subsequently, the MMPBSA scheme (Molecular Mechanics Poisson Boltzmann Surface Area) suggested three phytochemical compounds, C00000947, C00020451, and C00005031, with favourable binding affinity against WNK1. Among them, C00000947 acts as the most potent competitive inhibitor of WNK1. Further, inverse pharmacophore-based lead optimization of the C00000947 leads to one potential compound, meciadanol, which shows better binding affinity and specificity than C00000947 towards WNK1, which may be further exploited to develop effective therapeutics against WNK1-associated hypertension after in vitro and in vivo validation.